RANCANG BANGUN SISTEM PEMASARAN PROPERTI BERBASIS WEB - Arief Herdiansah; Tuti Handayani; Elsya Yunita (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Information technology is growing rapidly now, with technological advances everything can be achieved and reached very practically. Today many people spend their time using mobile phones / smartphones to view various online media, and one of them is advertising. PT Akila Trijaya is a property company, the company sees that currently the promotion method has not been carried out effectively, therefore the Company wants to utilize information technology in marketing its housing products known as Akila Residence in Serang City. To meet these needs, researchers took the initiative to design a web-based property information system created using the PHP programming language with the Mysql database. The researcher analyzes the current system using the SWOT analysis method. In the system design process, researchers use the Unified Modeling Language (UML) to create a marketing system design. The system testing method used is black box testing. This research has produced a web-based property marketing system that can help PT Akila Trijaya's to sell the Akila Residence.